Photoluminescence intensity of Cu-doped ZnO modulated via defect occupancy by applying electric bias. (4th August 2022) - Ho, Lok-Ping; Younas, Muhammad; Borgersen, Jon; Khan, Rao Tahir Ali; Rezvani, Seyed Javad; Pollastri, Simone; Akhtar, Muhammad Javed; Nadeem, Muhammad; Huang, Dong; Shi, Ying-Li; Kuznetsov, Andrej; Ling, Francis Chi-Chung
Abstract: Discovering multifunctional materials is of paramount importance for advancing the science and technology. Herein, we report on an optical phenomenon modulated by an electrical process that happened at the metal–ZnO:Cu junction, for which the light emission intensity from the photoluminescence is tuned reversibly by applying electric bias to the junction. Importantly, these observations were correlated with the x-ray absorption measurements, detecting prominent flips in Cu + /Cu 2+ oxidation state occupations in ZnO:Cu film as a function of the resistive switching. Moreover, further analysis of the x-ray absorption data revealed an additional prominent correlation—the signals interpreted as the Zn–O bond fingerprints also exhibited the modulations. By considering the whole set of data, we propose a scenario explaining the modulation phenomena.